Main characteristics of mineral manganese tailings pastes thickener prepared in laboratory scale - Olcay Barreda, R. H. (2014)
Tailings disposal in the form of mineral slurry has a number of advantages, among which we can highlight the environmental, social, operational and technical nature. This alternative arrangement of the tailings is a technology that has been developed rapidly highlighting the sector thickening equipment manufacturers and transportation. The main objective of this work was to evaluate the production of concentrated suspensions minerals known as pasta tailings from beneficiation processes manganese obtained by a paste thickener scale laboratory. The study includes the characterization of the solid sample, evaluation of flocculation (type and dosage), use of a producer of pulp laboratory scale equipment with a useful capacity of 7 liters for the formation of mineral paste through continuous feed of pulp, evaluation of influence on the solids concentration using generator floc (RGF), characteristics of mineral pulps produced as% of depression or slump, angle of repose or flume, solids concentration profile in the thickener, apparent viscosity and yield stress. Regarding the chemical composition it was obtained which are the predominant elements: Mn, Fe, Si and Al with a distribution fine grain size, represented by a d50 equivalent to 4,63μm. The nonionic flocculant was the one who showed best performance while settling in trials with recirculation pulp and flocculant addition, the best condition was reached for a recirculation of the lower zone and maximum layer Compression (4 to 1) obtaining a value of 53.7% solids by weight. In the continuous trials total duration of 180 minutes, the highest value reached% solids with a slurry feed linear flow was 52.7% for 50 gpt dose of flocculant. In feeding trials using curvilinear RGF a value of 55.5% it was obtained solids by weight; It was verified by means of the concentration profile of the compression zone there is a transitional stage pulp high density mineral pulp in the range of 40 to 45% solids by weight. The manganese tailings slurry form mineral between 47 and 56% solids by weight. They were hit angles of repose in the upper mineral pasta to 8th. The rheological behavior of all the tested pastes presented a mixed nature and reotrópico thixotropic. The yield stress reached values close to 100Pa to 56% solids by weight in the mineral pulp produced using the best operating conditions found in this study.